METODE BELAJAR KELASIK DALAM MEMBENTUK AHLAK DAN KECERDASAN SANTRI - Muhammad Mirwan Apriadi (An-Nahdlah: Jurnal Pendidikan Islam, 2023)
This research focuses on the following problem formulations: first, how do students and teachers find alternative ways that are easy but efficient for students and teachers to get maximum learning outcomes but not forgetting the morals as the hallmark of Islamic boarding schools, using classical learning methods, Research This study uses the Library Research approach, using the Library Research technique. In the data collection process, the authors use the Library Studies method. In this technique the author tries to include the advantages of learning by using the classical learning method. The data analysis technique used in this study consists of three phases: data reduction, data display and conclusion drawing. In this study the authors found that the use of the classical method is very beneficial if used in today's modern era, because if the use of this method is carried out properly and accurately, what students and students want will be achieved, after reading several magazines and articles we found many things that hinder learning, especially in the field of Ahlak,